The Asia-Pacific Stage: The Big Role and Geopolitical Challenges - Kunkunrat, Kunkunrat (SEAN Institute, 2022)
The geopolitical shift from Europe to the Asia Pacific region has made this region a hot area recently. Even though there is a race to increase maritime power, it is not yet considered an arms race. This research examines the major role and challenges of geopolitics on the Asia-Pacific Stage, a region that has a significant impact on global dynamics. This research uses a qualitative approach with descriptive methods. The research results show that the Asia-Pacific Stage is a complex stage with various geopolitical challenges. Territorial disputes, competition between major powers such as China, the United States and Russia, and the threat of terrorism create tensions that affect stability. The existence of nuclear weapons and the potential for proliferation increases the risk of serious conflict. Humanitarian crises, both due to conflict and the impact of climate change, add complexity to the increasing number of refugees. In this context, regional organizations such as ASEAN are emerging as key players in managing tensions. Overcoming these challenges requires joint efforts, careful diplomacy and international cooperation to maintain peace, security and sustainable development in the region.